Evaluation of the Level and Polymorphism of the Osteocalcin Gene in Patients with Rheumatoid Arthritis - Al-Jubouri, Saba M. M.; Al-Assie, Wasan N. H.; Al-Azzawi, Adnan F. N. (Journal for Research in Applied Sciences and Biotechnology, 2022)
The hormone is known as the bone protein γ-carboxyglutamic acid. The hormone belongs to the family of proteins that depend on vitamin K, as this vitamin is a catalyst in the formation of (γ-carboxylation) that determines its attraction to the bone matrix and calcium, and this contributes to the formation of bones. Moreover, the non-carboxylated form of the hormone that exerts hormonal properties and is also involved in glucose and energy metabolism, stimulates osteoblasts to secrete insulin directly and indirectly from the pancreas through the synthesis of glucagon-like-peptide 1 GLP-1 From the small intestine this enhances insulin sensitivity in fat cells and muscle cells. This property may have an effect on bone mineralization and may lead to a change in bone quality and an increased risk of fractures. The aim of the study is to evaluate the level of osteocalcin in patients with rheumatoid arthritis in comparison with the healthy ones and its relationship with the enzymes (GSH, CP, SOD), and to detect the gene encoding the hormone osteocalcin in the disease and to find the relationship between the hormone osteocalcin and vital variables. Blood samples were collected from (30) healthy people (15) males and (15) females, their ages ranged from (25-60) years and (30) patients from (19) males and (11) females in a hospital Salah Al-Din General and Al-Sharqat General Hospital, and the analyzes were measured in the central laboratory of the hospital, which were examined by the specialist doctor. This study showed that the levels of OC in the blood serum of people with rheumatoid arthritis is statistically higher compared to the healthy ones, and a significant decrease in the level of GSH for patients compared with the healthy ones, and a significant increase in the level of CP and the level of SOD for patients compared with the healthy ones, and there is a positive correlation between the level of OC and the level of CP And a negative relationship between OC level, GSH level and SOD level. It was revealed that there were significant differences at the level of probability (P<0.01) of repeating the allele for the OC gene between the group of patients and the healthy ones, where the value of the repeating of the mutated C allele increased and the level of the normal T allele decreased within the group of patients compared to the healthy ones.